Modern Constitutionalism as the Foundation of the Rule of Law: A Theoretical Review - Putri, Cory Kartika; Wachid Maulana; Ahmad Nuradi; Andi Adri Agus; Hardjito S. Darmojo (International Journal of Education, Vocational and Social Science, 2026)
Modern constitutionalism has evolved as a fundamental concept in contemporary state governance that emphasizes the need to limit governmental power through constitutional mechanisms. This study conducts a Systematic Literature Review (SLR) using PRISMA 2020 guidelines to analyze the development, foundational pillars, and implementation challenges of modern constitutionalism as the basis of the rule of law. Fourteen relevant articles published between 2010 and 2025 were selected through a systematic database search and eligibility screening. The findings show that modern constitutionalism consists of core elements such as the rule of law, separation of powers, human rights protection, and restorative constitutionalism, which together reinforce state legitimacy and accountability. Its implementation varies across jurisdictions depending on legal systems, institutional capacity, and technological advancements. Contemporary challenges including populism, globalization, and algorithmic governance highlight the urgency for adaptive and innovative constitutional strategies. This study concludes that modern constitutionalism is not only a normative framework but also a practical foundation for maintaining an effective and sustainable rule of law state. Keywords: modern constitutionalism, rule of law, separation of powers, restorative constitutionalism, democracy.